2019
DOI: 10.5194/amt-2019-82
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<i>A Tale of Two Dust Storms</i>: Analysis of a Complex Dust Event in the Middle East

Abstract: Abstract. Lofted mineral dust over data-sparse regions presents considerable challenges to satellite-based remote sensing methods and numerical weather prediction alike. The Southwest Asia domain is replete with such examples, with its diverse array of dust sources, dust mineralogy, and meteorologically-driven lofting mechanisms on multiple spatial and temporal scales. A microcosm of these challenges occurred over 3–4 August 2016 when two dust plumes, one lofted within an inland dry air mass and another embedd… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This highly researched dust event was featured in a special issue publication, with an overview of the project, case study meteorology, and comparisons to observations found in Miller et al. (2019), and additional model/observation evaluations of dust AOD presented in Saleeby et al. (2019).…”
Section: Case Study Model and Analysis Methodsmentioning
confidence: 98%
“…This highly researched dust event was featured in a special issue publication, with an overview of the project, case study meteorology, and comparisons to observations found in Miller et al. (2019), and additional model/observation evaluations of dust AOD presented in Saleeby et al. (2019).…”
Section: Case Study Model and Analysis Methodsmentioning
confidence: 98%